Vendor independent myocardial strain values in children. Issue 1 (7th December 2022) - Acheampong, Benjamin; Parra, David; Havens, Corey; Jantzen, David; Godown, Justin; Soslow, Jonathan
Abstract: Background: Two‐dimensional (2D) strain imaging has become an important tool in assessing subclinical myocardial dysfunction in children. However, there are no published normal values for vendor‐independent strain software. The aim of this study was to estimate 2D strain values in a cohort of healthy children using Tomtec cardiac performance analysis (CPA), a vendor‐independent software. Methods: Transthoracic echocardiograms of healthy pediatric outpatients (0–18 years) were retrospectively analyzed from the Vanderbilt Pediatric Heart Institute using CPA. The cardiac assessment included global longitudinal strain (GLS), global longitudinal strain rate (GLSR), global circumferential strain (GCS), and global circumferential strain rate (GCSR). Mean strain values with standard deviation (SD) are reported. The Wilcoxon rank sum test, linear regression, and one‐way analysis of variance were used to assess differences among the various groups. Results: Among 142 children analyzed, 79 (56%) were male, and the median age was 5.5 (range, 0–18) years. The mean (SD) strain values were GLS –19.3 ± 3.4, GLSR –1.1 ± .22; GCS ‐24.7 ± 4.3, GCSR –1.5 ± .28. Age accounted for <8% of the variation in GLS, GCS, and GCSR. However, for GLSR, there was a statistically significant difference between younger and older age groups with higher GLSR in the younger age group. Age accounted for ∼25% of the variation in GLSR (R 2  = .25, p  < 0.001). There were no significant differences in strain based on sex. Conclusion: We report normal myocardial strain values in healthy children by age for strain using CPA. These values add to the growing body of literature on myocardial strain in children and provide necessary data for the interpretation of strain imaging.